AB0845 Monographic Consultation of Patients with Knee Osteoarthritis with Joint Effusion: Specific Care Model. Experience After one Year. (9th June 2015) - Calvet Fontova, J.; Orellana, C.; Navarro, N.; García-Manrique, M.; Galisteo, C.; Gratacos, J.; Larrosa, M.
Abstract : Background: The management of knee osteoarthritis (KOA) is very heterogeneous. We have designed a monographic care model to visit these patients in preferential circuit. Objectives: To set up a preferential referral for patients with knee osteoarthritis when joint effusion is suspected. To assess synovial inflammation by ultrasound. To provide priority care for future flares. Redirect to the appropriate consultation if a different diagnosis is established. Methods: Patients were referred to a specific monographic consultation called OAREU from other members of the rheumatology department staff, from other hospital department and emergency department and from primary care consultancies The following variables were collected: 1. Anthropometric and sociodemographic. 2. General and locomotor physical examination. 3. Specific questionnaires for functional and clinical severity. 4. Presence and quantification of effusion and inflammation by ultrasound examination. 5. Arthrocentesis if synovial fluid present. In case of VASpain >4, intra-articular injection of glucocorticoids were administered. 6. Radiographic OA degree (Kellgren-Lawrence). 7. Basic blood and joint fluid analysis. 8. Satisfaction was measured by a Likert scale questionnaire. In addition, hygienic-dietary advice was provided. Patients were visited monthly until stabilization, and subsequently annual visits were scheduled. The model included telephone consultation in case of recurrence or flare of pain and/or inflammation, with priority visit if necessary. The effectiveness of infiltration therapy was assessed: if improvement >6 months it was considered effective, partially effective if improvement duration 3-6months, and ineffective if <3 months. Results: One hundred and eighty-three patients have been visited from October 2013 to December 2014 (average 13 visits/month). 137/183 were correctly referred with osteoarthritis radiology and ultrasound signs of synovial fluid or hypertrophy. In 99 joint fluid was obtained. 39 patients did not meet criteria for referral (3 inflammatory fluid, 36 radiology consistent with knee osteoarthritis but VAS pain less than 3 and/or without effusion). 14 had mechanical joint effusion with no osteoarthritis radiology (9 with no other cause for mechanical effusion during follow-up). 23/137 consulted a second time for recurrence of effusion (23.3%), 19 of them before 3 months, 3 between 3 and 6 months and 1 beyond 6 months. 6 have required a third infiltration and 4 patients more than 3 arthrocenthesis. 126/137 (91.9%) showed a good performance (VAS pain less than 4). The satisfaction degree with the monographic consultation model was high or very high in 96% of patients. Infiltration therapy was considered a good analgesic technique, with 87% of patients recommending it regardless of the result obtained in themselves. Conclusions: Flares of inflammation in knee osteoarthritis are frequent and justify the creation of a specific consultation with a preferential referral system for care and follow-up. This group of KOA patients may benefit from this model with preferential visit more than with a standard visit. According to the results of clinical improvement and patient satisfaction, this model appeared to be effective, improved patient care and allowed for systematic data collection. Disclosure of Interest: None declared